2006
DOI: 10.1002/cbf.1389
|View full text |Cite
|
Sign up to set email alerts
|

The FXIIIVal34Leu, common and risk factors of venous thrombosis in early middle‐age Costa Rican patients

Abstract: In this study, eight common polymorphisms associated with venous thrombosis (VT) and thrombophilia factors were analyzed in a Costa Rican case-control study. With the use of polymerase chain reaction (PCR) methods the polymorphisms were detected in 120 patients and 133 controls (mean age <40 years old). It was concluded that a high level of fibrinogen, antiphospholipid antibodies, family history, and the genotype 34LeuLeu of FXIII OR 0.42 (0.20-0.89) showed a significant effect on the risk of VT. Associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(26 reference statements)
0
9
0
1
Order By: Relevance
“…In that study, only 3 cases and 18 controls had the FXIII TT genotype (compared to our study with 24 cases and 65 controls). Salazar-Sanchez reported an inverse association of TT with VT among Latin American residents of Costa Rica, with only 4 cases and 13 controls being TT [6].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In that study, only 3 cases and 18 controls had the FXIII TT genotype (compared to our study with 24 cases and 65 controls). Salazar-Sanchez reported an inverse association of TT with VT among Latin American residents of Costa Rica, with only 4 cases and 13 controls being TT [6].…”
Section: Discussionmentioning
confidence: 97%
“…A common polymorphism in Factor XIII, a G100T substitution in exon 2 of the α-subunit resulting in a valine to leucine substitution at position 34 (FXIII Val34Leu), appears to lower the risk of VT, although not all studies agree [1][2][3][4][5][6]. A meta-analysis of 12 studies suggested a small inverse association [7].…”
mentioning
confidence: 99%
“…A major determining factor for clot morphology is the level of plasma fibrinogen, 16 which when elevated is an independent risk factor for cardiovascular disease. 17 Plasma fibrinogen has a high variation within the population and is affected by several factors such as seasonal variation, 18 smoking, 19 aging, and the presence of atherosclerosis. 17 The contribution of genetic factors to plasma fibrinogen levels has been estimated to be $30 to 50%.…”
Section: Fibrinogen Genetics and Thrombotic Riskmentioning
confidence: 99%
“…50 Several studies have found that the Leu allele is protective against MI and stroke. 18,51,52 However, protection appears to be lost in the presence of increasing degrees of insulin resistance and high levels of PAI-1. On a molecular basis, it was found that the Leu allele is activated by thrombin with a 2.5-fold increase in catalytic efficiency.…”
Section: Fibrinogen Genetics and Thrombotic Riskmentioning
confidence: 99%
“…La elevación plasmática de la protrombina se asocia con la inhibición de la proteína S, cofactor de la proteína C activada (PCA); también disminuye la actividad anticoagulante no dependiente de la PCA lo que aumenta el riesgo de trombosis (6,7). Así, los heterocigotos de la PTG20210A (G/A), presentan un incremento de 3 veces el riesgo de sufrir un evento trombótico venoso comparado con individuos normales homocigotos (G/G) [6,7,8,9]. La importancia de la mutación PT G20210A en la trombosis arterial aún no es suficientemente clara; algunos estudios sugieren que podría ser un riesgo de infarto agudo del miocardio (IAM) en fumadores jóvenes [8].…”
Section: Revista Electrónica Publicada Por La Escuela De Medicina De unclassified